2003
DOI: 10.1081/ja-120023394
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Sources of Measurement Error in Substance Use Surveys

Abstract: We present an overview of the cross-cultural quality of survey reports of substance use behaviors in the United States. Empirical data from 36 published studies (1977-2003) are examined to evaluate the reliability and validity of substance use reports across cultural groups. In these studies, race/ethnicity are used as proxy indicators of respondent culture. In general, the available research suggests that, with a few exceptions, the quality of survey data on racial and ethnic disparities in substance use is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 68 publications
5
43
0
Order By: Relevance
“…17 This model posits that race/ethnicity differences in underreporting reflect a divergence in values between African American and White respondents, especially with regard to privacy 18 and collectivism. 19 In support of this perspective, Johnson and Bowman 6 point out that research has suggested that African Americans have expressed more concerns about privacy and confidentiality in research than others. This model suggests that if race/ethnicity differences in substance abuse reporting validity exist, they may diminish in statistical models that control for respondent perceptions of privacy and question threat.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…17 This model posits that race/ethnicity differences in underreporting reflect a divergence in values between African American and White respondents, especially with regard to privacy 18 and collectivism. 19 In support of this perspective, Johnson and Bowman 6 point out that research has suggested that African Americans have expressed more concerns about privacy and confidentiality in research than others. This model suggests that if race/ethnicity differences in substance abuse reporting validity exist, they may diminish in statistical models that control for respondent perceptions of privacy and question threat.…”
Section: Introductionmentioning
confidence: 91%
“…15,16 Regarding the former, Johnson and Bowman 6 note that "the basic notion is that low income African-Americans are locked in a cycle of poverty primarily because they have a poverty of culture." Misleading survey reports regarding substance abuse behavior (i.e., substance use underreporting on surveys) are viewed as an outgrowth of culturally divergent values and norms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the proportion of Latinos with history of IDU (10%) was consistent with previous studies , IDU might be underreported among Latinos (Johnson and Bowman, 2003), particularly among those who are foreign-born and undocumented. Second, we were limited to using ZIP codes to define neighborhoods.…”
Section: Discussionsupporting
confidence: 62%